Optimization of the composition of fiber foam concrete with polypropylene fiber Fox Polfiber M12 produced by basf company - Ilyasov Allanazar; Adilkhodjaev Anvar; Makhamataliev Irkin; Allamuratov Allambergen (E3S Web of Conferences, 2023)
The results of experimental studies on optimizing the composition of non-autoclaved fiber foam concrete with polypropylene fiber Fox Polfiber M12 produced by BASF (Germany) and on determining its properties are presented in the article. A pattern was established for a decrease in shrinkage strain in non-autoclaved fiber foam concrete with an increase in the content of polypropylene fiber by weight and a reduction in cement consumption. At that, the least shrinkage strains in samples of fiber foam concrete were observed at a minimum content of mineral filler –micro-silica.